Homeobox-Only Protein Expression Is a Critical Prognostic Indicator of Pancreatic Neuroendocrine Tumor and Is Regulated by Promoter DNA Hypermethylation. Issue 9 (October 2016) - Ushiku, Hideki; Yamashita, Keishi; Kawamata, Hiroshi; Waraya, Mina; Katoh, Hiroshi; Yokoi, Keigo; Tanaka, Toshimichi; Ishii, Satoru; Nishizawa, Nobuyuki; Kikuchi, Mariko; Minatani, Naoko; Kojo, Ken; et al.
Abstract : Objectives: We have identified homeobox-only protein (HOPX) as a tumor suppressor gene in various human cancer, and its expression was reduced by promoter DNA hypermethylation. Homeobox-only protein is strongly expressed on pancreatic islet cells; however, clinical relevance of HOPX expression has remained elusive in pancreatic neuroendocrine tumor (pNET). Methods: We investigated 36 patients with pNET who undertook surgical resection between 1988 and 2012 for HOPX expression and DNA methylation to reveal its clinical significance. Results: (1) Homeobox-only protein is strongly expressed on pancreatic islet cells by immunohistochemistry (IHC). Homeobox-only protein expression was recognized on pNET tumor cells for 1+ in 15, for 2+ in 16, and for 3+ in 5. (2) Homeobox-only protein IHC expression was significantly associated with prognosis ( P = 0.03), and survival rate was 37.5%, 70.3%, and 100% in HOPX 1+, 2+, and 3+, respectively. (3) Promoter DNA methylation was quantitatively assessed, and HOPX hypermethylation is found in 6.3%, 11.8%, and 66.7% of G1/G2/G3 pNET, respectively ( P = 0.02). (4) Multivariate Cox proportional hazards model identified HOPX IHC expression and HOPX promoter DNA hypermethylation as independent prognostic factors in pNET. Conclusions: Homeobox-only protein expression is a critical prognostic indicator of pNET, and its regulation may be made through promoter DNA methylation. Abstract : Supplemental digital content is available in the text.